Предмет: Алгебра,
автор: nastyaorlova22
помогите 895:* Пожалуйста
Приложения:
Ответы
Автор ответа:
0
РЕШЕНИЕ
cosx + cos2x + cos3x + cos4x = ( cosx + cos4x) + (cos2x + cos3x) =
= 2*cos(x+4x)/2*cos(x-4x)/2 + 2cos(2x+3x)/2*cos(2x-3x)/2 =
= 2cos(5x/2)*(cos(=3x/2) - cos(-x/2) = 2*cos(5x/2)*(cos(3x/2) - cos(x/2))
cosx + cos2x + cos3x + cos4x = ( cosx + cos4x) + (cos2x + cos3x) =
= 2*cos(x+4x)/2*cos(x-4x)/2 + 2cos(2x+3x)/2*cos(2x-3x)/2 =
= 2cos(5x/2)*(cos(=3x/2) - cos(-x/2) = 2*cos(5x/2)*(cos(3x/2) - cos(x/2))
Похожие вопросы
Предмет: Математика,
автор: yan5415
Предмет: Информатика,
автор: uskimbaevtamirlan
Предмет: Физкультура и спорт,
автор: nailadauranova69
Предмет: Химия,
автор: Аноним
Предмет: Математика,
автор: jana2382